Science for behavioral health systems change: evolving research-policy-public partnerships - Southam-Gerow, Michael A.; Sale, Rafaella; Robinson, Ashley; Sanborn, Victoria; Wu, Juliet; Boggs, Brianna; Riso, Alana; Scalone, Marrin; Sandman, Ashley (Frontiers in Public Health, 2024)
Potent partnerships among researchers, policymakers, and community members have potential to produce positive changes in communities on a range of topics, including behavioral health. The paper provides a brief illustrative review of such partnerships and then describes the development and evolution of one partnership in particular in Virginia. The origin of the partnership is traced, along with its founding vision, mission, and values. Some of its several projects are described, including (a) needs assessment for implementation of evidence-based programs (EBPs) pursuant to the Family First Prevention Services Act; (b) statewide fidelity monitoring of key EBPs; and (c) projects to synergize state investments in specific EBPs, like multisystemic therapy, functional family therapy, and high fidelity wraparound. The paper concludes with some themes around which the center has evolved to serve the state and its citizens more effectively.